THREE LEVEL REPRESENTATION ORIENTED ELECTRONIC MODULE IN THE CONCEPT OF AMINE - Muchtar Arifin; Neneng Windayani; Saepudin Rahmatullah (Gunung Djati Conference Series, 2021)
Amina is one of the concepts in organic chemistry that is difficult for students to understand because it is abstract, so students cannot connect understanding between macroscopic-level phenomena, submicroscopic levels, and symbolic levels on the concept of amines. Therefore, it takes a learning medium that can help explain the three levels of representation interactively. The purpose of this research is to create electronic modules as a medium of interactive teaching materials as well as test their feasibility for use by students. The research method is done with research & development, which is to analyze what is needed by students, then create electronic modules, and then applied in learning. The research was conducted on third semester students who have studied organic chemistry. The results showed that the electronic modules created had an interactiveity so that students were able to understand the concept of amines with macroscopic, submicroscopic, and symbolic visualizations. Responders as much as 100% feel the benefits, interests, and motivation in using it. Based on appearance and content, responders rate 85% and 90% respectively. The conclusion is that this electronic module is worth using in studying the concept of amines.